A new near-IR luminescent erbium(III) complex with potential application in OLED devices - Martín-Ramos, Pablo (2013)
We report the synthesis and X-ray structural characterization of the new Er3+ ternary complex [Er(hd)3(bipy)] (where Hhd is 3,5-heptanedione and bipy is 2,2′-bipyridine) as well as its absorption/luminescent properties. X-ray analysis of the novel complex reveals its triclinic centrosymmetric structure with two symmetry independent complexes in the unit cell. Each lanthanide ion is surrounded by 6 oxygen atoms and 2 nitrogen atoms in a square antiprismatic geometry. The solid-state electronic absorption spectra and the luminescence spectrum show long-wavelength 4f–4f transitions which provide a potential use of the compound as a NIR emitting material in organic light-emitting devices (OLEDs).